Pathophysiological processes in multiple sclerosis: focus on nuclear factor erythroid-2-related factor 2 and emerging pathways - Arnold P; Mojumder D; DeToledo J; Lucius R; Wilms H (Dove Medical Press, 2014)
Philipp Arnold,1,* Deb Mojumder,2,* John DeToledo,2 Ralph Lucius,1 Henrik Wilms2 1Institute of Anatomy, Christian-Albrechts-University Kiel, Kiel, Germany; 2Department of Neurology, Texas Tech University Health Science Center, Lubbock, TX, USA *These authors contributed equally to this work Abstract: Multiple sclerosis (MS) is a disease of the central nervous system that is characterized by the demyelination of neuronal axons. Four different patterns of demyelination have been described, showing the heterogeneity in the immunopathologic processes involved in the demyelination. This review will focus on reactive oxygen species (ROS)-related inflammation in MS. Special emphasis will be placed on the nuclear factor erythroid-2-related factor 2 (Nrf2) as it regulates the transcription of ROS-protective genes. In the cytosol, Nrf2 binds to Keap1 (Kelch-like ECH-associated protein 1), and together they are degraded by the 26S proteasome after ubiquitination. If challenged by ROS Nrf2, binding to Keap1 is abrogated, and it translocates into the nucleus. Here it binds to the antioxidant response element and to a small protein termed Maf (musculoaponeurotic fibrosarcoma oncogene homolog). This leads to an enhanced transcription of ROS protective genes and represents the physiological answer against ROS challenge. It has been shown that dimethyl fumarate (DMF) has the same effect and leads to an enhanced transcription of ROS-protective genes. This response is mediated through a reduced binding of Nrf2 to Keap1, thus resulting in a higher level of free Nrf2 in the cytosol. Consequently, more Nrf2 translocates to the nucleus, promoting transcription of its target genes. DMF has been used for the treatment of psoriasis for many years in Germany without the occurrence of major side effects. In psoriasis, DMF reduces ROS-related inflammation in skin. A DMF analog, BG-12, was recently approved for the treatment of relapsing-remitting MS by the European Union and the US Food and Drug Administration. As an oral formulation, it gives patients a convenient and effective alternative to the injectable immune modulators in the long-term treatment of MS. Keywords: MS, fumaric acid ester, ROS